2000
DOI: 10.1677/joe.0.1660283
|View full text |Cite
|
Sign up to set email alerts
|

Role of 17beta-estradiol and/or progesterone on insulin sensitivity in the rat: implications during pregnancy

Abstract: The mechanism for the development of insulin resistance in normal pregnancy is complex and is associated with serum levels of both progesterone and 17 -estradiol. However, it remains unclear whether estrogens alone or progestins alone can cause insulin resistance, or whether it is a combination of both which produces this effect. We attempted to determine the role played by progesterone and/or 17 -estradiol on the phenomena of sensitivity to insulin action that take place during pregnancy in the rat. Ovariecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 47 publications
5
51
0
Order By: Relevance
“…Our results confirm that aging results in a significant increase in the basal levels of glucose, a fact that is exacerbated by ovariectomy. Moreover, as we expected, 1 h of estradiol treatment was enough to improve this parameter, a good evidence suggesting rapid or nongenomic actions of estrogen, as we previously showed (Alonso et al 2006a(Alonso et al ,b, 2008Gonzalez et al 2000, ) and estradiol-treated (E, ) and genisteintreated (G1, and G2, ) rats. Mean±SEM for seven animals.…”
Section: G1 Vs Eg2supporting
confidence: 74%
See 2 more Smart Citations
“…Our results confirm that aging results in a significant increase in the basal levels of glucose, a fact that is exacerbated by ovariectomy. Moreover, as we expected, 1 h of estradiol treatment was enough to improve this parameter, a good evidence suggesting rapid or nongenomic actions of estrogen, as we previously showed (Alonso et al 2006a(Alonso et al ,b, 2008Gonzalez et al 2000, ) and estradiol-treated (E, ) and genisteintreated (G1, and G2, ) rats. Mean±SEM for seven animals.…”
Section: G1 Vs Eg2supporting
confidence: 74%
“…Clamp experiments were performed in anesthetized rats using a previously described procedure (Alonso et al 2006a(Alonso et al , 2008Gonzalez et al 2000). After 12 h of fasting, animals were anesthetized with sodium pentobarbital (50 mg/kg), and the left saphenous vein was catheterized for insulin and glucose infusion.…”
Section: Euglycemic Insulin Clampmentioning
confidence: 99%
See 1 more Smart Citation
“…Clamp experiments were performed using a previously described procedure (González et al 2000), the results of which were published recently (Alonso et al 2006). Before and after the clamp study, blood samples for the determination of insulin and 17β-estradiol plasma concentrations were collected from the jugular vein into heparinized tubes, centrifuged at 3,000 rpm for 20 min at 4°C and plasma was immediately drawn off and stored frozen at −20°C until assayed.…”
Section: Euglycemic-hyperinsulinemic Clampmentioning
confidence: 99%
“…Experimental studies (González et al 2000(González et al , 2003Kumagai et al 1993) and clinical observations (Colacurci et al 1998;Karjalainen et al 2001) have demonstrated the importance of estrogen in the maintenance of insulin sensitivity in postmenopausal women. However, the route, dose and type of estrogen used appear to determine the efficacy of therapy.…”
Section: Introductionmentioning
confidence: 99%